Tetanus Toxsoid Immunization Counseling for Pregnant Women in Mangga Village, Medan Tuntungan District - Dwi Ris Hasanah; Nurdiana Manurung (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine whether pregnant women in Mangga output, Medan Tuntungan sub-district, had received tetanus toxoid immunization, and whether pregnant women had understood the usefulness of the immunization during pregnancy. And the activities carried out are increasing the knowledge of pregnant women about the importance of tetanus toxoid immunization, increasing the knowledge of husbands or families to assist mothers in routine pregnancy check-ups. The results of the research are To achieve the objectives of the above activities, activities were carried out including the delivery of material about the importance of tetanus toxoid immunization during pregnancy for pregnant women, the importance of husband or family support for mothers to visit routine pregnancy check-ups.